Measurements of aerosols and charged particles on the BEXUS18 stratospheric balloon - Brattich, Erika; Serrano Castillo, Encarnación; Giulietti, Fabrizio; Renard, Jean-Baptiste; Tripathi, Sachi N.; Ghosh, Kunal; Berthet, Gwenael; Vignelles, Damien; Tositti, Laura (Annales Geophysicae, 2019)
This paper describes the aerosol measurement setup and results obtained during the BEXUS18 (Balloon-borne Experiments for University Students) stratospheric balloon within the A5-Unibo (Advanced Atmospheric Aerosol Acquisition and Analysis) experiment performed on 10 October 2014 in northern Sweden (Kiruna). The experimental setup was designed and developed by the University of Bologna with the aim of collecting and analyzing vertical profiles of atmospheric ions and particles together with atmospheric parameters (temperature, relative humidity, and pressure) all along the stratospheric ascent of the BEXUS18 stratospheric balloon. Particle size distributions were measured with the MeteoModem Light Optical Aerosol Counter (LOAC) and air ion density was measured with a set of two commercial and portable ion counters. Though the experimental setup was based upon relatively low-cost and light-weight sensors, vertical profiles of all the parameters up to an altitude of about 27 km were successfully collected. The results obtained are useful for elucidating the relationships between aerosols and charged particles between ground level and the stratosphere, with great potential in collecting and adding useful information in this field, also in the stratosphere where such measurements are rare. In particular, the equipment detected coherent vertical profiles for particles and ions, with a particularly strong correlation between negative ions and fine particles, possibly resulting from proposed associations between cosmic rays and ions as previously suggested. In addition, the detection of charged aerosols in the stratosphere is in agreement with the results obtained by a previous flight and with simulations conducted with a stratospheric ion–aerosol model. However, further measurements under stratospheric balloon flights equipped with a similar setup are needed to reach general conclusions about such important issues.